Logic in Educational Research and Policy Making - Garlikov, Rick (Education Policy Analysis Archives, 2000)
While educational research is an empirical enterprise, there is significant place in it for logical reasoning and anecdotal evidence. An analysis of the article by Scott C. Bauer, "Should Achievement Tests be Used to Judge School Quality?" (Education Policy Analysis Archives, 8(46). Available: http://epaa.asu.edu/v8n46.html) is used to illustrate this point.